Intraocular lens implantation in developmental lens disorders in children - Kanigowska, Krystyna; Grałek, Mirosława; Kępa, Beata; Chipczyńska, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The pediatric cataract surgery in eyes with developmental disorders, stay with still considerable challenge. At children, the lasting vision development extorts necessity quick settlement of refraction defect formed after operation. The intraocular lens implantation after cataract extraction is the best method of visual rehabilitation. Authors present surgical procedure in 3,5 years old boy with cataract in microspherophakia and 12 years old boy with cataract in lens with coloboma. One-piece flexible and rigid PMMA intraocular lens was placed with success at posterior chamber without scleral fixations and without using capsular tension ring in this cases. After 3 years of observation there were no decentration or dislocation of intraocular lens in both children. Authors concluded that in some cases posterior chamber intraocular lens implantation despite defective zonular or capsular support, can make up the effective method of surgical treatment without risk of early dislocation.